1990
DOI: 10.1038/jcbfm.1990.8
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cerebral Hypothermia during and after Cardiac Arrest Improves Neurologic Outcome in Dogs

Abstract: Summary: We previously found mild hypothermia (34-36°C), induced before cardiac arrest, to improve neu rologic outcome. In this study we used a reproducible dog model to evaluate mild hypothermia by head cooling dur ing arrest, continued with systemic cooling (34°C) during recirculation and for 1 h after arrest. In four groups of dogs, ventricular fibrillation (no flow) of 12.5 min at 37 SC was reversed with cardiopulmonary bypass and defibrillation in �5 min, and followed by controlled ven tilation to 20 h an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(129 citation statements)
references
References 49 publications
2
118
1
5
Order By: Relevance
“…12 The few studies that attempted intra-arrest hypothermia have demonstrated encouraging protection patterns. Leonov et al 13 performed external cranial intra-arrest cooling in a canine model of cardiac arrest, with additional cooling provided by cardiac bypass. Cooling in this combined fashion was more protective than normothermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The few studies that attempted intra-arrest hypothermia have demonstrated encouraging protection patterns. Leonov et al 13 performed external cranial intra-arrest cooling in a canine model of cardiac arrest, with additional cooling provided by cardiac bypass. Cooling in this combined fashion was more protective than normothermia.…”
Section: Discussionmentioning
confidence: 99%
“…9,[13][14][15] The theoretical advantages to cooling before ROSC may include decreasing reperfusion-related injury. Protective cellular mechanisms consistent with this concept include attenuation of the oxidant burst seen within minutes of normothermic reperfusion or the inhibition of reperfusion-activated apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The animal model used for these studies has been used extensively by us and others to study global cerebral ischemia and reperfusion [15][16][17][18][19][20]. Adult purebred female beagles weighing 10-15 kg were anesthetized initially with an intravenous injection of veterinary thiopental (8-12 mg/kg).…”
Section: Canine Cardiac Arrest Modelmentioning
confidence: 99%
“…The use of moderate hypothermia after cardiac arrest was initially reported in the late 1950s and early 1960s [75,76]. There were no further investigations conducted on hypothermia as a resuscitative measure until the 1990s, when laboratory studies demonstrated the benefit of mild hypothermia [77][78][79][80]. These studies led to the preliminary clinical research on mild hypothermia.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%